2016
DOI: 10.1515/afe-2016-0063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cooling Rate on Properties of Intermetallic Phase in a Complex Al-Si Alloy

Abstract: The cooling rate is one of the main tools available to the process engineer by means of which it is possible to influence the crystallisation process. Imposing a desired microstructure on a casting as early as in the casting solidification phase widens significantly the scope of technological options at disposal in the process of aluminium-silicon alloy parts design and application. By changing the cooling rate it is possible to influence the course of the crystallisation process and thus also the material pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The increasing content of Fe leads to formation of, especially, iron-rich phases in form of needles, then it in forms into skeleton-like shapes. Skeleton-like shapes were not observed in alloys B and C. These findings correlate with research work of authors [12][13][14]. The authors confirmed that the higher the iron content, the longer and wider the needles.…”
Section: Microstructure Of Experimental Materialssupporting
confidence: 88%
See 3 more Smart Citations
“…The increasing content of Fe leads to formation of, especially, iron-rich phases in form of needles, then it in forms into skeleton-like shapes. Skeleton-like shapes were not observed in alloys B and C. These findings correlate with research work of authors [12][13][14]. The authors confirmed that the higher the iron content, the longer and wider the needles.…”
Section: Microstructure Of Experimental Materialssupporting
confidence: 88%
“…Most negative are iron-rich intermetallic phases. In Fe-containing aluminum cast alloys, Fe-rich intermetallic phases are formed, such as β-Al [12][13][14][15]. The Chinese script morphology of the α-iron phase occurs during eutectic solidification.…”
Section: Microstructure Of Experimental Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several intermetallic phase particles, like Al 3 Mg 2 , Mg 2 Si, Al 2 CuMg, and MgZn 2 are anodic to the aluminum matrix and corrode preferentially with respect to the aluminum matrix, while the particles like AlFeMnSi, AlCuFeMn, Al 2 Cu (θ phase) and AlCuFeSi are found to be cathodic with respect to the aluminum matrix and cause peripheral trenches in the aluminum matrix adjacent to the intermetallic particles [7]. Iron, which is major class of secondary phase (AlFe and/or AlFeSi), induces a decrease of both mechanical and corrosion resistance properties but it reduces the tendency to adhere to metal molds [8]. The anodic behavior of intermetallic particles regarding the aluminum matrix can cause localized corrosion [9].…”
Section: Introductionmentioning
confidence: 99%